Diversity of bacterial symbionts associated with the tropical plant bug Monalonion velezangeli (Hemiptera: Miridae) revealed by high-throughput 16S-rRNA sequencing - Navarro-Escalante, Lucio; Benavides, Pablo; Acevedo, Flor E. (Peer Community Journal)

(untitled)
Insects and microbes have developed complex symbiotic relationships that evolutionarily and ecologically play beneficial roles for both, the symbiont and the host. In most Hemiptera insects, bacterial symbionts offer mainly nutritional, defensive, and reproductive roles in addition to promoting the adaptive radiation of several hemipteran phytophagous lineages. The tropical plant bug Monalonion velezangeli (Hemiptera: Miridae) is a polyphagous herbivore considered an important insect pest for several economically relevant tropical crops, but information about the composition of its bacterial microbiota was missing. In this study, we describe the diversity and structure of the bacterial microbiota in the nymph and adult life stages of M. velezangeli using Illumina high-throughput sequencing of 16S ribosomal RNA gene amplicons (meta-barcoding). We found that both insect life stages share a similar microbiota in terms of bacterial diversity and community structure. The intracellular symbiont Wolbachia dominated the overall microbiome composition (~92%) in these life stages. Members of the core microbiota include Wolbachia, Romboutsia, Ignavibacterium, Clostridium, Allobaculum, Paracoccus, Methylobacterium, Faecalibacterium, Collinsella, Rothia, Sphingomonas and 4 other undetermined bacterial genera. Based on PCR screening and DNA sequencing of the wsp gene, Wolbachia infection was confirmed in almost 80% of samples, and represented by two different isolates or strains within the supergroup B. This data offers opportunities for studying the contribution of symbiotic bacteria in the biological performance of this insect pest, and provides a base to explore other insect control methods.